Does Income Inequality Make Us Less Happy?. (March 2015) - Nguyen, Jeremy K.; Fleming, Christopher M.; Su, Jen‐Je
Abstract This article presents evidence from Australia showing linkages between income inequality in an individual's geographical region and life satisfaction. Higher income inequality is associated with lower self‐rated life satisfaction. In contrast to expectations that inequality may primarily be an issue of concern for poorer individuals, the relationship holds strongly for higher income households, but the evidence for lower income households is less conclusive. Shadow price estimates indicate that, in order to offset the effect of annual changes in inequality over the sample period (2001–2009), an average Australian would require compensatory changes of approximately 3–9 per cent in income each year (about $3, 689 in 2009).